Diez años del Instituto Universitario de Desarrollo y Cooperación - Gamo Rodríguez, Alfonso (Revista Española de Desarrollo y Cooperación, 2023)
The article summarizes the activities carried out by the IUDC over ten years, with a special focus on the fields in which the added value of this institution (research work, postgraduate training, technnical assistance and dissemination) has make significant contribution to improve the effectiveness of aid.